Systematic Literature Review (SLR) of Urban Temporality Flexible and Adaptive Spatial Design Strategies in Urban Context - Khansa Aulia Ekaputri; Arnis Rochma Harani; Asrul M. R Aminuddin (Universitas Sebelas Maret Surakarta, 2025)
Urban temporality has become an emerging field of study in architecture and urban design, offering new perspectives on understanding urban space. However, systematic reviews of the evolution of this discourse remain limited. This study applies a Systematic Literature Review (SLR) using the PRISMA methodology to analyze the development of the concept of urban temporality in academic literature over the past decade. 200 publications containing